PENYULUHAN PENTINGNYA KEBERSIHAN LINGKUNGAN DI DESA MUARA SANDING KECAMATAN GARUT KOTA - Hasbi Taobah Ramdani; Andhika Lungguh Perceka; N. Ai Erlinawati; Herlin Rusyani (Jurnal Pengabdian Masyarakat DEDIKASI, 2021)
Non-communicable diseases (NCDs) are the leading cause of death in the world. PTM can be detected by early detection by checking blood pressure, blood cholesterol levels, blood sugar and measuring BMI. The purpose of this activity is to detect non-communicable disease risk factors early after an examination has been carried out. This activity was carried out using a rapid test method for checking cholesterol, blood sugar, while blood pressure was checked using a digital sphygmomanometer, and height and weight were measured to obtain BMI data. The activity is carried out in December 2021-January 2022. The location of the activity is RW 15, Sindanggalih Village, Karangpawitan, Garut Regency with 50 participants. The results of the examination obtained as many as 25 people (50%) had prehypertension. Examination of blood cholesterol levels showed that 20 people (40%) had hypercholesterolemia. As many as 61 people (61%) are not sure to have DM and the results of BMI measurements are 23 people (23%) at risk of obesity. This detection through routine health checks is very necessary to find out from the start there are risk factors for a person to suffer from non-communicable diseases or not.